Valence shell electronically excited states of 1-phenylimidazole and 1-benzylimidazole - Powis, I.; Shaw, D. A.; Townsend, D.; Holland, D. M. P. (Molecular physics, 2025)
The valence shell electronically excited states of 1-phenylimidazole and 1-benzylimidazole have been studied by employing synchrotron radiation to measure the absolute photoabsorption cross-section of each molecule, from threshold up to an energy of 10.8 eV. Assignments have been proposed for some of the broad absorption bands using calculated transition energies and oscillator strengths. Natural transition orbital plots have allowed the Rydberg and/or valence character of the electronically excited states to be assessed. Some of the calculated transitions in 1-benzylimidazole and 1-phenylimidazole have initial and final orbitals that are analogous to those of transitions in the isolated constituent rings of imidazole and benzene. Other mixed Rydberg/valence transitions, especially those leading to some of the low energy electronically excited states in 1-phenylimidazole, have an initial orbital located on the imidazole ring while valence character in the final orbital is localised on the phenyl ring. Thus, photoexcitation results in charge transfer from the donor site (imidazole) to the acceptor (the phenyl ring) in the nascent ion core of the Rydberg state. In both 1-benzylimidazole and 1-phenylimidazole the lowest energy excited state arises from a transition analogous to the 1e 1g → 1e 2u 1B 2u electric dipole-forbidden transition in benzene.